BIM for energy certification in AEC industry: bibliometric analysis of four certificate cases - Idrissi Gartoumi, Khalil; Radoine, Hassan; El Ghazouani, Laila (Frontiers in Built Environment, 2025)
The Architecture, Engineering, and Construction (AEC) industry is widely acknowledged for its substantial impact on energy consumption. Building Information Modeling (BIM), as a promising avenue to address the imperative of reducing energy consumption has been explored with sustainability frameworks but in specific areas, especially in its 6th dimension. Despite its potential, the literature shows that the connection between BIM and various environmental standards and certifications remains one of the least explored and utilized aspects. This study aims to identify commonalities in the application of BIM and environmental certifications, shedding light on both academic and practical gaps in the environmental management of buildings. To achieve this, a bibliometric literature review is conducted. Given the limited number of previous reviews, this study provides updated and original insights, serving as a foundational resource for future investigations into automated energy requirements. The research results reveal the four most widely adopted certifications, offering a substantial contribution to both the scientific community and AEC industry practitioners. The study provides a comprehensive and in-depth understanding of the current state of the link between BIM and Green Building Certifications (GBCs). Despite the restriction on the databases selected and focusing on the most common certifications, this study gives insight into the use of BIM with a certification that can be efficient when used in conjunction with another to better optimize environmental impact throughout the life cycle. Moreover, it underscores the low rate of automation in GBCs credits and requirements, emphasizing the necessity to incorporate new technologies like the Internet of Things (IoT) and blockchain into the field.